Influencer Credibility, AI Personalization, and Authenticity Affect Trust, Purchase Intention, Loyalty among Brazilian Fintech Users - João Carlos da Silva; Mariana Oliveira Santos; Rafael Pereira Costa (ICON Publisher, 2026)
This study examines how social media influencer credibility, AI-powered personalization, and brand authenticity shape customer trust and subsequent behavioral outcomes among Brazilian fintech users. Using survey data and structural equation modeling, the research tests a trust-centered framework linking three contemporary marketing drivers to purchase intention and brand loyalty through an intervening trust mechanism. The results indicate that all three antecedents significantly enhance customer trust, confirming the relevance of social, technological, and symbolic cues in digital financial services. Customer trust, in turn, strongly predicts both purchase intention and brand loyalty, highlighting its dual role in short-term adoption and long-term relationship formation. These findings demonstrate that fintech marketing effectiveness depends on the integration of credible social influence, intelligent personalization, and authentic brand communication. The study contributes theoretically by extending trust-based marketing models into fintech contexts and by clarifying how multiple digital signals converge to influence behavior. Managerially, the results suggest that fintech firms should prioritize influencer selection, invest in explainable AI personalization, and communicate transparent brand values to strengthen trust. Despite its contributions, the study is limited by its cross-sectional design and self-reported data. Future research may apply longitudinal approaches, compare countries, and incorporate actual usage behavior.